2008
DOI: 10.1021/es702363e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface Oxides on the Adsorption of Naphthalene onto Multiwalled Carbon Nanotubes

Abstract: As greater quantities of carbon nanotubes (CNTs) enter the environment, they will have an increasingly important effect on the availability and transport of aqueous contaminants. As a consequence of purification, deliberate surface functionalization, and/or exposure to oxidizing agents after release to the environment, CNTs often contain surface oxides (i.e., oxygen containing functional groups). To probe the influence that surface oxides exert on CNT sorption properties, multiwalled CNTs (MWCNTs) with varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
226
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(241 citation statements)
references
References 48 publications
14
226
0
Order By: Relevance
“…The peak located at 1462 cm -1 could be attributed to carbonyl groups [19]. The absorptions at 1384 cm -1 were associated with symmetric COO -stretching [2,20,21]. These produced functional groups abundantly on the external and internal surfaces of acidified functionalized MWCNTs, which can provide numerous chemical sorption sites and thus increase the ion exchange capacity for the metal ion, in other words, the hydrophilic properties of these functional groups improve the dispersity of MWCNTs in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…The peak located at 1462 cm -1 could be attributed to carbonyl groups [19]. The absorptions at 1384 cm -1 were associated with symmetric COO -stretching [2,20,21]. These produced functional groups abundantly on the external and internal surfaces of acidified functionalized MWCNTs, which can provide numerous chemical sorption sites and thus increase the ion exchange capacity for the metal ion, in other words, the hydrophilic properties of these functional groups improve the dispersity of MWCNTs in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, oxidation with nitric acid increased the sorption of p-xylene, while decreasing the sorption of o-xylene on singlewalled carbon nanotubes (SWCNTs), suggesting that the sorption of o-xylene and p-xylene onto SWCNTs was mainly influenced by the positions of the methyl groups on xylene molecules and the presence of oxygen-containing groups on the surface of SWCNTs [5]. However, a recent study [8] revealed that incorporated surface oxides on CNTs created polar regions that reduced the surface area available for naphthalene sorption, and that as little as a 10% increase in surface oxygen concentration resulted in a 70% decrease in the maximum sorption capacity of naphthalene. This study indicated that oxidative treatments may not always beneficially enhance sorption of organic compounds and pointed to the need to investigate sorption of specific compounds on a case by case basis.…”
Section: Introductionmentioning
confidence: 94%
“…Due to their high surface area and large micropore volume, CNTs are also considered to be extremely good adsorbents and since the first report of their successful removal of dioxins [1], CNTs have been utilized for the sorption of a large number of different organic compounds from water [2][3][4][5][6][7][8]. The sorption properties of CNTs can be modified by chemical oxidation treatments using sodium hypochlorite (NaOCl), hydrogen peroxide (H 2 O 2 ), potassium permanganate (KMnO 4 ), and nitric acid (HNO 3 ) [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotube surface areas are typically in the range of 290  170 m 2 /g (mean  standard error) (Cho et al, 2008). By comparison, AC surface areas range from 800-1200 m 2 /g (Cooper and Alley, 2002).…”
Section: Adsorption On To Carbon Nanotubesmentioning
confidence: 99%